Helicobacter pylori stimulates dendritic cells to induce interleukin-17 expression from CD4+ T lymphocytes. - Khamri,W; Walker,MM; Clark,P; Atherton,JC; Thursz,MR; Bamford,KB; Lechler,RI; Lombardi,G (Infect Immun, 2010)
Helicobacter pylori is a human gastroduodenal pathogen that leads to active chronic inflammation characterized by T-cell responses biased toward a Th1 phenotype. It has been accepted that H. pylori infection induces a Th17 response. At mucosal sites, dendritic cells (DCs) have the capacity to induce effector T cells. Here, we evaluate the role of DCs in the H. pylori-induced interleukin-17 (IL-17) response. Immunohistochemistry and immunofluorescence were performed on human gastric mucosal biopsy samples and showed that myeloid DCs in H. pylori-infected patients colocalized with IL-23- and that IL-17-producing lymphocytes were present in H. pylori-infected antral biopsy samples. In parallel, human monocyte-derived DCs stimulated in vitro with live H. pylori cells produced significant levels of IL-23 in the absence of IL-12 release. The subsequent incubation of H. pylori-infected DCs with autologous CD4(+) T cells led to gamma interferon (IFN-gamma) and IL-17 expression. The inhibition of IL-1 and, to a lesser extent, IL-23 inhibited IL-17 production by T cells. Finally, isogenic H. pylori mutant strains not expressing major virulence factors were less effective in inducing IL-1 and IL-23 release by DCs and IL-17 release by T cells than parental strains. Altogether, we can conclude that DCs are potent inducers of IL-23/IL-17 expression following H. pylori stimulation. IL-1/IL-23 as well as H. pylori virulence factors seem to play an important role in mediating this response.